2021
DOI: 10.3389/fmolb.2021.628386
|View full text |Cite
|
Sign up to set email alerts
|

3D Cell Culture for the Study of Microenvironment-Mediated Mechanostimuli to the Cell Nucleus: An Important Step for Cancer Research

Abstract: The discovery that the stiffness of the tumor microenvironment (TME) changes during cancer progression motivated the development of cell culture involving extracellular mechanostimuli, with the intent of identifying mechanotransduction mechanisms that influence cell phenotypes. Collagen I is a main extracellular matrix (ECM) component used to study mechanotransduction in three-dimensional (3D) cell culture. There are also models with interstitial fluid stress that have been mostly focusing on the migration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 110 publications
0
7
0
Order By: Relevance
“…Plasma‐induced apoptosis in tumoursphere was previously shown to depend on H 2 O 2 , NO 2 − , and NO 3 − and it is demonstrated that these diffuse longer distances than short‐lived species, such as O 2 − , OH•, and ONOOH/ONOO − . [ 28,30 ] In our case, cell‐permeable NAC is protective, yet catalase was unable to fully protect cells from CAP, indicating that reactive species other than hydrogen peroxide also play a role in the 3D tumoursphere model. Therefore, the response of U‐251 MG tumourspheres to CAP is different from previous reports, and indeed to U‐251 MG cells grown in 2D cultures where we found, using the same plasma system where CAP treatment induced predominantly H 2 O 2 ‐dependent cytotoxicity.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…Plasma‐induced apoptosis in tumoursphere was previously shown to depend on H 2 O 2 , NO 2 − , and NO 3 − and it is demonstrated that these diffuse longer distances than short‐lived species, such as O 2 − , OH•, and ONOOH/ONOO − . [ 28,30 ] In our case, cell‐permeable NAC is protective, yet catalase was unable to fully protect cells from CAP, indicating that reactive species other than hydrogen peroxide also play a role in the 3D tumoursphere model. Therefore, the response of U‐251 MG tumourspheres to CAP is different from previous reports, and indeed to U‐251 MG cells grown in 2D cultures where we found, using the same plasma system where CAP treatment induced predominantly H 2 O 2 ‐dependent cytotoxicity.…”
Section: Resultsmentioning
confidence: 76%
“…The tumor microenvironment plays a key role in tumor progression, metastasis, angiogenesis, cytotoxicity resistance, and immune cell modulation. [27,28] We employed a U-251 MG 3D cell culture model, which enabled cell-cell and cell-ECM interactions in all three dimensions and mimicked diffusion-limited distribution of oxygen, nutrients, metabolites, and signaling molecules common in the microenvironment of in vivo tumors. Most of the research on the effects of CAP on cancer cells has been investigated by using 2D monolayer cell cultures [29,30] and a growing number of animal models.…”
Section: Pin-to-plate Discharge Presents Cytotoxicity Toward Gbm Cell...mentioning
confidence: 99%
“…GBM is distinguished by increased vascularization, significant cell heterogeneity, self-renewing cancer stem cells and the interactions between tumour and microenvironment, all of which contribute to tumour progression [ 25 ]. Tumour development, metastasis, angiogenesis, cytotoxicity resistance, and immune cell modulation are all influenced by the tumour microenvironment (TME) [ 10 , 26 ]. There is a gap in mostly accessible GBM pre-clinical models and 3D cell culture is able to fill this gap by providing more reliable models to study the correlation between TME, tumour reoccurrence and therapy resistance.…”
Section: Methodsmentioning
confidence: 99%
“…This study supports the idea that the histone methylation landscape is affected by the culture microenvironment. Clearly, it is necessary to study in more detail how mechanotransduction in 3D culture influences cell nuclear phenotypes since the epigenetic organization strongly depends on tissue architecture [ 181 , 182 , 183 ].…”
Section: Microenvironment and Nutritional Influence On The Preservati...mentioning
confidence: 99%